Sending of Unwanted Dick Pics as a Modality of Sexual Cyber-Violence: An Exploratory Study of Its Emotional Impact and Reactions in Women - Durán Penedo, Mercedes (Journal of interpersonal violence, 2023)
The sending of sexually explicit images by men to women without prior request, a practice commonly referred to as sending or receiving a “dick pic,” is a fairly common manifestation of sexual cyber-violence that has grown in recent times. As research on this type of sexual cyber-violence is limited, the current study analyzed the prevalence of this phenomenon in a sample of 347 Spanish women between 18 and 30 years of age, studying the factors that influence the emotional impact reported by women if they received an unsolicited dick pic (using a hypothetical scenario) and exploring the various coping strategies that women would use in that situation. Results showed a significant prevalence of this type of cyber-violence in the sample, as 48.1% of the participants had received an unsolicited dick pic from an unknown man at some point. Women with lower levels of hostile sexism—but not of benevolent sexism—reported a higher depressed and angry/annoyed emotional impact of the sexual cyber-violence scenario. This was also the case for women with a less conservative political ideology, with less religious beliefs, as well as those women who perceived that their female friends receive this type of images frequently (descriptive norm) and who perceived that their female friends are less accepting of these situations (injunctive norm). In addition, from the strategies presented to the participants to cope with this situation of sexual cyber-violence, it was observed that a significant percentage of women would choose strategies, such as talking about the incident with other people and blocking the sender’s access. Yet, fewer women would employ effective strategies, such as reporting the perpetrator’s profile to the managers or administrators of the social network or reporting the incident to the police. This study is one of the first studies in Spain that addresses this new form of sexual cyber-violence against women by unknown men and suggests that, in online social networks, women experience the same situations of abuse, harassment, and sexual objectification that they have faced offline in everyday life. Therefore, more work needs to be done to raise awareness and try to prevent these situations, while also providing more support to these women so that they can adopt effective coping strategies.